Skill-based English Language Teaching Programs’ Issues and Merits in Higher Education: A Systematic Literature Review - Febriyanti Utami; Sri Sumarni; Darmahusni Darmahusni (Universitas Muhammadiyah Semarang, 2023)
Skill-based English language teaching (ELT) programs offer various learning opportunities for learners to master the skills in using the language. However, research on the challenges of such programs is still scarce in literature. Therefore, this study was aimed to examine recent research articles on the implementation of skill-based ELT programs in higher education in terms of the types of skills featured in the programs, the issues, and the merits of the programs. The study employed a systematic literature review. The reviewed articles were retrieved from 2014 to 2022 using digital paper search tools and filtered systematically using exclusion and inclusion criteria. A total of twenty-five manuscripts were included and analysed under the three key points: types of skills featured in the ELT programs, issues related to the implementation of skill-based ELT programs, and merits of the programs. The results showed that the majority of studies covered multiple skills, with only seven studies reporting one skill taught in the programs. Interestingly, there were only six studies which reported the issues of the programs, while twenty reviewed articles discussed the merits. The issues revealed from the study were categorised into those related to students, teachers, and course materials; some of which were specified as materials in the syllabuses and diverse students’ backgrounds. The study found out that the advantages of using skill-based approach in ELT outweighed the drawbacks since it could help students develop skills more accurately, deepen knowledge, improve technology literacy, accommodate their needs, and enjoy the lessons. With this study, a further investigation on the development of the program design is suggested, particularly in designing skill-based programs which enable learners to use the learned skills and knowledge in real-life situations.